Handmade Flashcards for Developing English Comprehension of Rural EFL Young Learners - Ahmad, Kuni Salsabila; Aisyah, Siti; Prasetyo, Yudy; Putranto, Henry Rio (Academy of Education Journal, 2024)
This research investigates the effectiveness of handmade flashcards as a teaching tool to improve English comprehension among rural EFL young learners. It aims at enhancing vocabulary retention and overall language comprehension by providing a hands-on, visually appealing learning experience. The research also addresses the lack of resources and engagement in rural EFL classrooms, bridging the gap through innovative approaches. It has implications for EFL teaching practices in rural settings, highlighting handmade flashcards as practical and accessible resources to address resource limitations. The qualitative method as research design involves data collection, classroom observations, and interviews. The sample comprises rural EFL young learners aged 12-13 from diverse backgrounds, ensuring representation of various factors affecting English comprehension. The research findings show that handmade flashcards had positive impact on the students. They exhibited increasing engagement, vocabulary retention, and better understanding of sentence structures and context. Peer interactions, fostering collaboration, and communication skills are also encouraged. These ideas can facilitate vocabulary acquisition, active learning, and language development among young learners. Further exploration and implementation of such innovative materials to support effective EFL instruction in developing English comprehension of rural areas should be conducted, ultimately for empowering both teachers and Young Learners.